Hailey Hailey-a blooming disease - Sadasivam, Ilakkia P.; Jagadeeshkumar, Govardhan; Paquirissamy, Oudeacoumar; Dileep, Jude E.; Takharya, Rajkiran; D'souza, Lisa J. (International Journal of Research in Dermatology, 2021)
Hailey Hailey disease (HHD) is a rare genetic disorder which is more common in summers. It involves intertriginous areas of the body. Axilla, abdomen, back, nape of neck are the common sites involved. We hereby present three patients of HHD from same geographical area with no blood relation. Two of them had other family members also involved with the similar complaints. One of the patients is 50 years of age. Diagnosis was done both by clinical and histopathological examination. It showed epidermis with intraepidermal bulla and acantholytic keratinocytes giving dilapidated brick wall appearance. Treatment mainly used was topical steroids &antihistamines and patients responded well.